A Heterogeneous Layer-Based Trustworthiness Model for Long Backhaul NVIS Challenging Networks and an IoT Telemetry Service for Antarctica - Adrià Mallorquí; Agustín Zaballos (Sensors, 2021)
Antarctica is a key location for many research fields. The lack of telecommunication systems that interconnect remote base camps hardens the possibility of building synergies among different polar research studies. This paper defines a network architecture to deploy a group of interconnected remote Antarctic wireless sensor networks providing an IoT telemetry service. Long backhaul NVIS links were used to interconnect remote networks. This architecture presents some properties from challenging networks that require evaluating the viability of the solution. A heterogeneous layer-based model to measure and improve the trustworthiness of the service was defined and presented. The model was validated and the trustworthiness of the system was measured using the Riverbed Model simulator.